2019
DOI: 10.3847/1538-4357/ab24de
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Highly Blueshifted Broad Balmer and Metastable Helium Absorption Lines in a Tidal Disruption Event

Abstract: We report the discovery of non-stellar hydrogen Balmer and metastable helium absorption lines accompanying a transient, high-velocity (0.05c) broad absorption line (BAL) system in the optical spectra of the tidal disruption event (TDE) AT2018zr (z = 0.071). In the HST UV spectra, absorption of high-and low-ionization lines are also present at this velocity, making AT2018zr resemble a low-ionization broad absorption line (LoBAL) QSO. We conclude that these transient absorption features are more likely to arise … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 93 publications
7
43
0
Order By: Relevance
“…For example, the likely presence of P λ1118 3 in iPTF15af suggests a column density of N H > 10 23 cm −2 (Blagorodnova et al 2019). A similar constraint has been obtained for AT2018zr from the detection of BAL signatures in Balmer and metastable Helium lines (Hung et al 2019). From a modelling perspective, Roth & Kasen (2018) have shown that the detailed line profile shapes seen in TDEs can be understood if these features are formed in an optically thick outflow.…”
Section: The Optical Depth Of Disc Winds In Tdessupporting
confidence: 52%
See 4 more Smart Citations
“…For example, the likely presence of P λ1118 3 in iPTF15af suggests a column density of N H > 10 23 cm −2 (Blagorodnova et al 2019). A similar constraint has been obtained for AT2018zr from the detection of BAL signatures in Balmer and metastable Helium lines (Hung et al 2019). From a modelling perspective, Roth & Kasen (2018) have shown that the detailed line profile shapes seen in TDEs can be understood if these features are formed in an optically thick outflow.…”
Section: The Optical Depth Of Disc Winds In Tdessupporting
confidence: 52%
“…Compton heating and inverse Compton cooling are also included, together with Auger ionization and dielectronic recombination (see Higginbottom et al 2013). (Brown et al 2017b;Blagorodnova et al 2017); and AT2018zr (Hung et al 2019), observed at similar post-flare epochs. Also included is a composite LoBALQSO spectrum (Brotherton et al 2001) and a rest-frame UV spectrum of the Nitrogen rich QSO SDSS J 164148.19 +223225.22 (Batra & Baldwin 2014).…”
Section: Radiative Transfer and Ionizationmentioning
confidence: 63%
See 3 more Smart Citations